Mekanisme Koping Pada Pasien Terdiagnosa Kanker Paru di Rumah Sakit Islam Surakarta - WIDARINI, SINTA RAHMANIA AYU, Arum Pratiwi, S.Kp., M.Kes (2015)
Lung cancer is a disease that has a high morbidity almost worldwide. Based on preliminary studies conducted in RS Islam Surakarta, in 2013 there were 115 lung cancer hospitalization patients, 2014 there were 374 patients, in 2015 up to 15 June 2015 amounted to 148 patients. The average age of patients with lung cancer between 40 - 65 years and the majority of patient's gender are male. Loss Individual response reactions is very different and specific. Theory Engel (1964) in Potter & Perry (2005) a process of grieving or loss through three phases,first is denying, second is began to feel lost and may feel desperate, then began to accept the loss of existing and slowly rose to face facts that occurred. According to Kubler-Ross (1969) in Potter & Perry (2005) stages a person grieving the first denial, anger and bargaining; the second process of depression; third acceptance phase. This is qualitative research using method of grounded theory. The study population was patients with lung cancer who underwent outpatient or inpatient in Rumah Sakit Islam Surakarta who meet the inclusion criteria. The sample used was 5 respondents with a sampling technique that uses purposive sampling. Instrument of data collection was a researcher. Data collection tools to assist researchers are recorders and interview guidelines regarding coping mechanisms of lung cancer. Data analyses have several stages there are data organization, data reduction, coding, categorizing and theme determination. There are four themes that researcher found from this research, first is psychological impact, second is spiritual beliefs, third is physiological impact and fourth is chemotherapy impact. In the study conducted at Rumah Sakit Islam Surakarta obtained adaptive responses in spiritual beliefs and the chemotherapy impact. Mal adaptive response was found in the psychological and physiological effects.